The Influence Of Social Media, Celebrity Endorsers And Product Quality On Consumer Buying Interest In Dabe Beauty Products In Jakarta - Zed, Etty Zuliawati; Tri Mulyani Kartini; Pupung Purnamasari (SEAN Institute, 2024)
In order to cope with the increasing consumer interest in skincare products, companies are required to be more innovative and creative in competing in the market. Advances in technology and social media allow the cosmetics industry to grow rapidly. Through social media, consumers can easily search and get products that suit their needs. Dabe Beaute creates innovative products and utilises social media as a promotional tool that provides information about the variety of products and their quality. This research method uses quantitative methods with ‘nonprobability sampling’ sampling techniques, namely purposive sampling. Data collection techniques through distributing online questionnaires to 100 respondents and processed with SPSS version 25. The analysis method used is multiple linear regression. The results of hypothesis testing show that Social Media and Celebrity Endorser have a significant effect on Purchase Intention, while product quality has no significant effect on Purchase Intention of Dabe Beaute skincare in the city of Jakarta. Companies should expand research by adding other factors besides social media, celebrity endorsers and product quality that can influence buying interest.